2008
DOI: 10.1093/toxsci/kfm312
|View full text |Cite
|
Sign up to set email alerts
|

A Biologically Based Dose-Response Model for Dietary Iodide and the Hypothalamic-Pituitary-Thyroid Axis in the Adult Rat: Evaluation of Iodide Deficiency

Abstract: A biologically based dose-response (BBDR) model was developed for dietary iodide and the hypothalamic-pituitary-thyroid (HPT) axis in adult rats. This BBDR-HPT axis model includes submodels for dietary iodide, thyroid-stimulating hormone (TSH), and the thyroid hormones, T(4) and T(3). The submodels are linked together via key biological processes, including (1) the influence of T(4) on TSH production (the HPT axis negative feedback loop), (2) stimulation of thyroidal T(4) and T(3) production by TSH, (3) TSH up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 62 publications
2
44
0
2
Order By: Relevance
“…Furthermore, rats are more convenient for consecutive blood sampling. As a consequence, rats were widely used in other studies on the thyroid [19][20][21][22] . In this study, we successfully collected sufficient blood samples from each rat by subclavian venous puncture instead of other, more invasive or even fatal methods at the end of the 12th, 18th and 24th weeks, and, therefore, greatly avoided interindividual variation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rats are more convenient for consecutive blood sampling. As a consequence, rats were widely used in other studies on the thyroid [19][20][21][22] . In this study, we successfully collected sufficient blood samples from each rat by subclavian venous puncture instead of other, more invasive or even fatal methods at the end of the 12th, 18th and 24th weeks, and, therefore, greatly avoided interindividual variation.…”
Section: Discussionmentioning
confidence: 99%
“…Iodide ions excreted in urine is the result of metabolic processing of thyroid hormones or due to an excess in plasma concentration after an increase in oral iodine uptake (43). It was reported that about 95% of the daily iodide intake in rats was excreted in urine (11). However, this percentage can change significantly in case of iodide deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, thyroid hormones are responsible for the normal development and regulation of brain, neurons, and processes that involve cerebral functions (10). A unique and specific mechanism that regulates thyroid hormones is the hypothalamic-pituitary-thyroid (HPT) axis which, as the name indicates, incorporate the hypothalamus, the pituitary gland, and the thyroid gland into forming a loop mechanism that keeps the concentration of these hormones at normal levels (11). This mechanism is initiated with the detection of low levels of thyroid hormones by the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothalamic-pituitary-thyroid (HPT) axis controls many physiologic functions, including metabolism, development, and reproduction. A biologically based dose-response (BBDR) model for adult rats includes submodels for dietary iodide, thyroid-stimulating hormone (TSH), and the thyroid hormones thyroxine (T4) and 3,5,3′- triiodothyronine (T3) [27, 28]. The independently developed individual submodels were linked together to form the endogeneous BBDR-HPT axis model.…”
Section: A Biologically Based Dose-response (Bbdr) Model Of Hypothmentioning
confidence: 99%